An Analysis of Taboo Types Comments in Kompas TV Twitter Account about The Governor of Lampung - Tasya Amelliya Kharisma Putri; Rosita Ambarwati (SEMINAR NASIONAL SOSIAL, SAINS, PENDIDIKAN, HUMANIORA (SENASSDRA), 2023)
: The current people on the internet uttered a lot of harsh words when respond to something. This is a common phenomenon among Twitter users. They tend to express their annoyance, anger and disappointment with harsh words. The comments of Indonesian netizens on Twitter which lead to bad words aimed to the Governor of Lampung during Jokowi's visit to Lampung. This analysis aims to find out some of the taboo words that are widely used by Indonesian netizens on social media in expressing their anger and disappointment towards a phenomenon. This analysis is qualitative method by collecting data taken from Kompas Tv Twitter Account which analysed using Wardhaugh's theory. The results of the analysis of comments on Twitter media found 4 types of taboo according to Wardhaugh (1986), which are 1) Taboo words related to human body parts found 8 data, 2) Taboo words related to sex found 1 data, 3) Taboo words related to excretion found 1 data, and 4) Taboo words related to animal found 1 data. Based on the results of the analysis found, it proves that most Indonesian netizens express their anger and disappointment in harsh words related to the human body parts which is the brain.